The Implementation of Communicative Language Teaching (CLT) in Teaching English - Jabri, Umiyati; Samad, Ita Sarmita (Maspul Journal of English Studies, 2021)
This research was aimed at finding out the way of the teacher in implementing of Communicative Language Teaching (CLT) in teaching English at class of SMPN 1 Enrekang, exploring the media, problems, and types of CLT activities that students prefer. The population of this research was the teachers and the students of SMPN 1 Enrekang. The sample was three teachers and two classes. In this research, the data were obtained through three kinds of instruments namely, observation checklist, interview, and questionnaire. The result showed the ways of teacher in implementing of CLT were the teachers used principles of CLT methodology stated by Richards (2006:13). Moreover, the researcher found two other ways. Firstly, the teacher always tried to use creative ways/activities in applying Richards’s principles of CLT methodology in order not only to motivate and interest but also to decrease the boredom of students in learning English. Secondly, the teacher showed her sympathy, sensitivity, and understanding to their students’ needs and problems. Generally the problems encountered by the teachers were the students rarely communicated with others using English in daily life so they are lack of English proficiency. The media used by teacher were authentic materials, non-authentic material, listening exercises, internet, and computer based program. The result of questionnaire calculation is about 49.71. This result is in like categories as stated in Liker scale. Based on the data, the top rank of CLT activities that students prefer was task completion activities (100% of students).